Job Involvement in Leadership Style: A Case Study at the Technical Institute / Nineveh - Mahmood, Khalida Othman (International Journal of Psychosocial Rehabilitation, 2020)
The study focuses on revealing the role of the leadership style in the organization under research, determining the level of job involvement among employees at the technical institute in Nineveh, suggesting techniques to encourage job involvement among employees at institutes and especially the technical institute in Nineveh, and solving the problems of job involvement encountered by employees. The study has reached the result that there is a moral relationship between job involvement and the style of leadership. The study has also come up with the result that individuals feel with real pleasure at work at the institute and it has got the highest positive assessment. The highest negative assessment can be represented by the sentence ( I feel with psychological rest when dealing with my boss at work ). Other aspects which can be represented in the following (my colleagues help me at work, my boss gives me much freedom at work, my job preoccupies me even after finishing it, I feel lively when doing my job, and I invest most of my scientific ability and job experience at work) have got an intermediary one. The study recommends that it is necessary to make a periodic measure to gauge the involvement level at work to know and consolidate the positive aspects and also to know and treat the negative aspects. The study calls the institute administration to hold periodic meetings to discuss those issues that are related to the job and it also calls for the necessity of disseminating the theme of helping one’s colleagues at work and to work in teams, besides teaching employees how to invest their skills and abilities at work via training and continual rewards.